Digitalization of Cracker Sales Transactions through QRIS as an Effort to Introduce Non-Cash Payments for MSMEs - Alexander Adrian Saragi; Fitri Rahmawati Nasution; Margaret Stevani; Muh. Aryanugraha Ismajaya; Farhah Utami (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
This community service activity was carried out with the aim of introducing and training the use of QRIS (Quick Response Code Indonesian Standard) to MSME cracker sales in Tulungagung as an alternative to a non-cash payment system. So far, the cracker sales transaction process has been carried out entirely in cash, so business actors do not have the knowledge or experience in using digital payment methods. In fact, the development of the digital economy in Indonesia shows a significant increase in the use of QR-based payments, especially in the MSME sector. Through this activity, participants were given an understanding of the basic concept of digital payments, the benefits of QRIS for small business actors, and the technical stages of its registration and use through banking applications and digital wallets. The implementation method consists of socialization, training on the practice of creating a QRIS merchant account, and transaction simulation using the devices of each participant. The results of the activity indicated that all participants were able to create a QRIS account independently, understand how to make and receive payments, and realize that the non-cash method can be a practical, safe, and efficient option for their business. This activity is the first step to increase digital financial literacy for MSME actors in the traditional food sector, as well as open up opportunities for them to be integrated into the national digital economy ecosystem.